Analysis of Work Motivation and Compensation in an Effort to Increase Employee Morale at Barracuda Barbershop in Lamongan - Joko Wasono; Abid Muhtarom; Mohammad Yaskun (Sean Institute, 2025)
This research uses qualitative research which is a research method based on the philosophy of post-positivism, used to research on the condition of natural objects, (as opposed to experiments where the researcher is the key instrument, sampling of data sources is carried out purposively and snowball, collection techniques with tri-analysis data analysis are inductive or qualitative, and the results of this research emphasize meaning rather than generalization. Research results from facts that occur in the field show that providing motivation to employees has a considerable role in increasing the work morale of employees. Providing motivation by giving awards for every achievement that has been made by employees is intended to motivate the work spirit of employees, both outstanding and non-achievers, so that they can improve their performance like their colleagues who have received awards. The conclusion of the results is that work motivation and compensation play a role in efforts to increase employee morale, as the main factor that is the driving force in efforts to increase the morale of employees of Barracuda Barbershop is the provision of compensation given to employees and the researcher suggests that the provision of motivation is given with various new formulas to employees, which is focused on the development of knowledge and insight of employees Barracuda Barbershop. This motivation can be provided in the form of training or seminars that contain outside the world of Barbershop work. For example, with training on the business world, this is so that employees have the spirit to continue to develop.